Understanding the significance roles of altruism and sociodemographic factors on volunteering commitment / Mohd Nazir Rabun and Makmor Tumin - Rabun, Mohd Nazir; Tumin, Makmor (2019)
The growing awareness of volunteerism has made volunteerism as an issue on the global scale. In relation to this, the essential role of volunteerism in the modern society has been the subject of increased attention by many leaders. It was well captured in the first 1988 presidential debate when President Bush of the United States of America stressed on the prevalence of the voluntary sector in helping the government to solve many of its domestic problems such as poverty, school dropouts, crime and substance abuse (Turiman Suandi, 1991). Based on the report by Independent Sector (2001) as cited in Mardhiyyah Shari et al. (2013), the volunteering activities carried out through non-profit organisations in the US have been estimated to be equivalent to 9 million full time jobs. It is perceived that volunteering activities are crucial within America. Moreover, volunteerism has been evident to be an integral part of the social and economic landscape of Australia. It is reported by the Australian Bureau of Statistics [ABS], (2007) that approximately 713 million hours were spent on volunteering annually. Mardhiyyah Shari et al. (2013) also found that a survey in the UK suggested that volunteering was worth up to 40 billion pounds per annum, making it the third largest contributor to the nation's Gross Domestic Product. All those reported cases of volunteering work all over the world are overviewed and discussed to provide a better prospect and a deeper understanding on how those developed countries view and perceive volunteerism.